The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.5194/bg-9-2033-2012
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack concentrations and estimated fluxes of volatile organic compounds in a boreal forest

Abstract: Abstract. Soil provides an important source of volatile organic compounds (VOCs) to atmosphere, but in boreal forests these fluxes and their seasonal variations have not been characterized in detail. Especially wintertime fluxes are almost completely unstudied. In this study, we measured the VOC concentrations inside the snowpack in a boreal Scots pine (Pinus sylvestris L.) forest in southern Finland, using adsorbent tubes and air samplers installed permanently in the snow profile. Based on the VOC concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…Altogether, these observations suggest the accumulation of these compounds under or into the snow pack. The same phenomena have been verified in another study (Aaltonen et al, 2012). A similar comparison was performed for aldehydes identified and measured in the same sampling period.…”
Section: Vocs During a Snow Melt Eventsupporting
confidence: 76%
See 1 more Smart Citation
“…Altogether, these observations suggest the accumulation of these compounds under or into the snow pack. The same phenomena have been verified in another study (Aaltonen et al, 2012). A similar comparison was performed for aldehydes identified and measured in the same sampling period.…”
Section: Vocs During a Snow Melt Eventsupporting
confidence: 76%
“…Carbonyl compounds, such as aldehydes, are also important to atmospheric chemistry due to their atmospheric photolysis, reaction with hydroxyl and nitrate radicals, and their contribution to new particle formation (Atkinson, 2000;Jang and Kamens, 2001). Aldehydes can be directly emitted to the atmosphere from incomplete combustion of biomass and fossil fuels, by vegetation, when exposed to stress conditions such as ozone exposure or insect and pathogen attacks, and formed in the atmosphere as a result of photochemical oxidation of reactive compounds (Altemose et al, 2015;Wildt et al, 2003). Primary emissions of saturated C 6 -C 10 aldehydes, such as hexanal, heptanal, octanal, nonanal and decanal, were found from several particular plant species (Wildt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that boreal forest floor BVOC emissions peak during early summer and autumn (Aaltonen et al, 2011) and not at midsummer even though the green plant biomass is peaking at midsummer. BVOC emissions can even be measured from the snowpack during winter (Helmig et al, 2009; Aaltonen et al, 2012). In this work we focus on BVOC emissions both from soil and the whole ecosystem in a period of the year which has hither-to been largely neglected, namely the shoulder periods between summer and winter.…”
Section: Introductionmentioning
confidence: 99%
“…Although the inhibitory effect of CO 2 on the process level may be important, Arctic greening may strongly enhance the production of BVOCs in northern ecosystems (Arneth et al, 2007;Sun et al, 2013). Open tundra may also act as a significant source for BVOCs, especially if the snow cover period changes (Aaltonen et al, 2012;Faubert et al, 2012). This would lead to negative climate feedbacks involving either aerosol-cloud or aerosol-carbon cycle interactions (M. Kulmala et al, 2013Paasonen et al, 2013).…”
Section: Changing Land Ecosystem Processesmentioning
confidence: 99%